(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
New derivatives of 5-oxotetrahydrofuran were syntesized by efficient and convenient reactions from 2-(2,2-dimethyl-5-oxotetrahydrofuran-3-yl)acetyl chloride.